The Effect of Management Effectiveness and FFB Weighing Efficiency at the Palm Oil Mill Weighing Bridge on the Acceleration of FFB Purchases at PT Anj Agri Binanga - Djurmiani Nasution; Tri Inda Fadhila Rahma; Kusmilawaty (Amkop Management Accounting Review (AMAR), 2025)
This study aims to determine the analysis of the efficiency of the use of technology on the weighbridge of palm oil mills on the speed of purchasing FFB at PT ANJ Agri Binanga both partially and simultaneously. This research method is with a quantitative approach. Multiple regression analysis techniques with variables of effectiveness, efficiency and acceleration of purchases. The results of this study indicate that Effectiveness that meets the "INDUSTRIAL STANDARD" that high weighing efficiency (>50 tons/hour/unit) contributes to an increase in processing effectiveness of 5-8%. "MEDIUM" acceleration of FFB purchases will impact the performance of PT ANJ Agri Binanga so that it has an impact on the economic value of the Company. High acceleration of purchase (>15%) without capacity increase can reduce processing effectiveness by 3-5%. Increasing capacity synchronized with accelerated purchasing can maintain or increase processing effectiveness. Statistical results show that partially effectiveness has a positive but insignificant effect on the acceleration of FFB purchases and efficiency has a positive and significant effect on the acceleration of FFB purchases. Simultaneously effectiveness and efficiency 88.61% affect the acceleration of FFB purchases at PT ANJ Agri Binanga and the F test of the Ha hypothesis is accepted that effectiveness and efficiency together have a significant effect on the acceleration of FFB purchases at PT ANJ Agri Binanga located in Simangambat District, North Padang Lawas Regency.